Fault geometry and slip rates from the Nullarbor and Roe Plains of south‐central Australia: Insights into the spatial and temporal characteristics of intraplate seismicity. Issue 2 (23rd November 2022) - Sellmann, Schirin; Quigley, Mark; Duffy, Brendan; Yang, Haibin; Clark, Dan
Abstract: Analysis of TanDEM‐X and Shuttle Radar Topography Mission (SRTM) data reveals geomorphic evidence for 292 fault‐propagation fold scarps across the Miocene Nullarbor and Pliocene Roe Plains in south‐central Australia. Vertical displacements (VD) are determined using topographic profiling of a subset ( n  = 48) of the fold traces. Fault dips (mean = 44 +16/−14° at 1σ) are estimated from seismic reflection data; the mean dip is assigned to faults with unknown dip and combined with VD to estimate net displacements (ND) and average net displacements (AD) for each fault. AD exceeds single‐event displacements estimated from fault‐length scaling regressions, indicating the identified faults have hosted multiple earthquakes. Combining AD with (i) faulted surface ages (Nullarbor ~10–5 Ma, Roe ~2.5 Ma), (ii) ages of faulted erosional–depositional features (e.g. relic Late Miocene dune fields and Pliocene paleochannels), and (iii) onset of the neotectonic regime in Australia at ~10 Ma yields average slip rates from <0.1 m Myr −1 to >17 m Myr −1 (mean = 1.1 m Myr −1 ). Summation of displacements across faults yields crustal horizontal shortening rates lower than geodetically detectable resolution (≤0.01 mm yr −1 ) since the Late Miocene. The ca. 10 Myr‐long record of neotectonic faulting on the Nullarbor Plain provides important insights into earthquake spatial–temporal behaviours in a slowly deforming intraplate continental region. Abstract : We found structural–geomorphic evidence for 292 reverse fault‐propagation fold scarps dispersed across the surfaces of the Miocene Nullarbor and Pliocene Roe Plains in south‐central Australia. Total average displacements indicate the identified folds have hosted multiple surface‐rupturing earthquakes. Crustal shortening since the Late Miocene is ≤0.01 mm yr −1 (Nullarbor and Roe Plains) and lower than the minimum resolution of geodetic surveys. This provides a useful supplementary estimate of intraplate deformation in slowly deforming cratonic regions.